Influence Growth Economy, Products Gross Regional Domestic Product (GRDP) and Open Unemployment Rate Against Community Welfare with Human Development Index (HDI) As Moderating Variables - Nikmah, Umdatul Ulin; Setiawan, Ananda (Terbuka Journal of Economics and Business, 2025)
This study aims to analyze the effect of economic growth, Gross Regional Domestic Product (GRDP), and open unemployment rate on public welfare, with the Human Development Index (HDI) as a moderating variable. The main topic discussed is how these macroeconomic variables affect public welfare as measured by the achievement of HDI as an indicator of quality of life. This study uses a quantitative approach with moderated regression analysis to test the interaction between independent variables and moderating variables. The data used are sourced from the official report of the Central Statistics Agency (BPS) consisting of panel data with a time series for the period 2020-2023 and cross-sectional data from 34 provinces in Indonesia. Data processing was carried out using Moderate Regression Analysis (MRA) through Eviews 12 software. The results of the study show that economic growth has a negative and significant effect on public welfare, GRDP has a negative and insignificant effect on public welfare, while the open unemployment rate has a positive and insignificant effect on public welfare. The Human Development Index can moderate the relationship between economic growth and public welfare, but cannot moderate the relationship between GRDP and the open unemployment rate on public welfare.